Dynamic Changes in Antithyroperoxidase and Antithyroglobulin Antibodies Suggest an Increased Risk for Abnormal Thyrotropin Levels - Li, Yongze; Teng, Di; Guan, Haixia; Li, Yushu; Teng, Xiaochun; Yu, Xiaohui; Mao, Jinyuan; Shi, Xiaoguang; Fan, Chenling; Shan, Zhongyan; Teng, Weiping (Frontiers in Endocrinology, 2020)
Background Antithyroperoxidase (TPOAb) and antithyroglobulin (TgAb) antibodies are associated with abnormal thyrotropin (TSH) levels. However, the effect of dynamic changes in TPOAb and TgAb on incident abnormal TSH is unknown. Methods A total of 2387 euthyroid participants aged 18 years or older from three rural areas in northern China were enrolled in this cohort study. Questionnaire interviews and laboratory measurements were performed at baseline in 1999 and at follow-up in 2004. Multinomial logistic regression was used to examine the relationship between changes in thyroid antibodies and incident abnormal TSH levels. Results In this 5-year follow-up study, TPOAb tier gain was significantly associated with an increased risk of subnormal TSH levels (adjusted RR, 1.535; 95% CI: 1.357-1.736) and supranormal TSH levels (adjusted RR, 1.378; 95% CI: 1.196-1.587), and TgAb tier gain was significantly associated with an increased risk of supranormal (adjusted RR, 1.090; 95% CI: 1.007-1.179) TSH levels. Both thyroid antibody-positive seroconversion and persistent positivity were significantly associated with an increased risk of incident abnormal TSH levels. Thyroid antibody positive seroconversion was associated with a higher risk of incident subnormal TSH than incident supranormal TSH, whereas persistent positive thyroid antibody was associated with a higher risk of incident supranormal TSH than incident subnormal TSH. Conclusions Dynamic thyroid antibody changes may be related to incident abnormal TSH levels. Those with persistent positive thyroid antibody were more likely to have supranormal TSH than subnormal TSH, and those with positive seroconversion were more likely to have subnormal TSH than supranormal TSH. Further studies are needed to confirm this conclusion and to explore this association mediated by TSH receptor antibodies.